Cyclophilins A and B oppositely regulate renal tubular epithelial cell phenotype. (12th March 2020) - Sarró, Eduard; Durán, Mónica; Rico, Ana; Bou-Teen, Diana; Fernández-Majada, Vanesa; Croatt, Anthony J; Nath, Karl A; Salcedo, Maria Teresa; Gundelach, Justin H; Batlle, Daniel; Bram, Richard J; Meseguer, Anna
Abstract: Restoration of kidney tubular epithelium following sublethal injury sequentially involves partial epithelial–mesenchymal transition (pEMT), proliferation, and further redifferentiation into specialized tubule epithelial cells (TECs). Because the immunosuppressant cyclosporine-A produces pEMT in TECs and inhibits the peptidyl-prolyl isomerase (PPIase) activity of cyclophilin (Cyp) proteins, we hypothesized that cyclophilins could regulate TEC phenotype. Here we demonstrate that in cultured TECs, CypA silencing triggers loss of epithelial features and enhances transforming growth factor β (TGFβ )-induced EMT in association with upregulation of epithelial repressors Slug and Snail. This pro-epithelial action of CypA relies on its PPIase activity. By contrast, CypB emerges as an epithelial repressor, because CypB silencing promotes epithelial differentiation, prevents TGFβ -induced EMT, and induces tubular structures in 3D cultures. In addition, in the kidneys of CypB knockout mice subjected to unilateral ureteral obstruction, inflammatory and pro-fibrotic events were attenuated. CypB silencing/knockout leads to Slug, but not Snail, downregulation. CypB support of Slug expression depends on its endoplasmic reticulum location, where it interacts with calreticulin, a calcium-buffering chaperone related to Slug expression. As CypB silencing reduces ionomycin-induced calcium release and Slug upregulation, we suggest that Slug expression may rely on CypB modulation of calreticulin-dependent calcium signaling. In conclusion, this work uncovers new roles for CypA and CypB in modulating TEC plasticity and identifies CypB as a druggable target potentially relevant in promoting kidney repair. Graphical abstract: